An internship in psychiatric genetic counseling: Impact on genetic counseling graduates' practice and career choices. Issue 5 (19th April 2022) - Van den Adel, Brianna; Inglis, Angela; Austin, Jehannine
Abstract: Though psychiatric genetic counseling has been shown to have meaningful positive impacts on patient outcomes, there is currently only one specialist psychiatric genetic counseling clinic (located in Vancouver, BC). The service is inconsistently offered elsewhere, leaving this patient population largely underserved. In an effort to expand psychiatric genetic counseling, the clinic in Vancouver has been providing specialist internship training to genetic counseling students since 2012. This study explored the impact of the internship training on genetic counseling graduates' careers. Using an interpretive description approach, we recorded and transcribed interviews with past interns. Coding and data analysis were conducted concurrently. The interview guide was iteratively revised through the interview process and memoing was used to record ideas about the data and interviews throughout. From interviews with 15 past interns, we generated a theoretical model—'a fragile dream, easily broken'—describing the impact of the training on participants' careers. Completing an internship in psychiatric genetic counseling positively influenced participants' desire to provide psychiatric genetic counseling; however, most were unable to find work in the subspecialty. Some participants made efforts to create specialist positions for themselves, but setbacks and hurdles left many feeling defeated, resulting in them accepting established roles in other disciplines. We contextualize our findings in a discussion of what may be needed in order to successfully expand psychiatric genetic counseling.